PENGARUH SERVICE QUALITY, BRAND IMAGE, DAN RELIGIUSITAS TERHADAP LOYALITAS NASABAH BANK BSI CABANG KENDARI - Muljibir Rahman; Rusdin Muhalling; Elfinasari Elfinasari; Miftahur Rahman Hakim (JASIE, 2022)
This study aims to determine the effect of Service Quality, Brand Image and Religiosity on Customer Loyalty of Bank BSI (Study on BSI KC Kendari A Silondae 2). This study uses a quantitative method because it aims to confirm the data obtained in the field with the existing theory. Samples were obtained by 97 BSI customer respondents using simple random sampling technique. As for the technique of data collection is done by using the questionnaire method. Data was processed using validity test, reliability test, classic assumption test, and hypothesis testing using IBM SPSS 26 program. The results of this study indicate that Service Quality and Religiosity do not significantly influence BSI Customer Loyalty variables. Meanwhile, Brand Image has a positive and significant effect on BSI Customer Loyalty.